2022
DOI: 10.1111/dth.15540
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin as chemoprophylaxis for cutaneous malignancies in Muir‐Torre syndrome: A novel concept

Abstract: Muir-Torre syndrome (MTS) is an autosomal dominant cancer syndrome that is a phenotypic variant of hereditary nonpolyposis colorectal carcinoma (HNPCC), or Lynch syndrome. MTS is characterized by sebaceous neoplasms and HNPCC-associated malignancies such as colorectal, endometrial, and urothelial carcinomas. The Amsterdam criteria require the presence of at least one sebaceous adenoma, sebaceous epithelioma, sebaceous carcinoma, or keratoacanthoma (KA) with sebaceous differentiation in addition to a HNPCCassoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…More, oral chemoprophylaxis with retinoids (isotretinoin) for cutaneous tumours prevention could be an option for these patients. Other options include subcutaneous Interferon 2alpha and topic applications of retinoids (21)(22)(23)(24). A more recent breakthrough in this area are vaccines for immunoprevention of DNA mismatch repair deficient cancers, which show promising results in initial phases (25).…”
Section: Discussionmentioning
confidence: 99%
“…More, oral chemoprophylaxis with retinoids (isotretinoin) for cutaneous tumours prevention could be an option for these patients. Other options include subcutaneous Interferon 2alpha and topic applications of retinoids (21)(22)(23)(24). A more recent breakthrough in this area are vaccines for immunoprevention of DNA mismatch repair deficient cancers, which show promising results in initial phases (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although the beneficial effect of isotretinoin for MTS patients is described previously, 3,4 it is not routinely offered to these patients. An overview of doses used in these cases has been provided by Joshi et al 5 We found that the isotretinoin improved cosmesis and made clinical follow-up easier. New lesions were detected earlier, and suspicious lesions stood out more.…”
mentioning
confidence: 87%
“…Isotretinoin was chosen for its greater sebostatic effect when compared to other oral retinoids. 5 With the reduction in both the severity and the number of skin lesions, it is suspected that even the development of skin malignancies may be reduced. 3 Our patient reported improved quality of life since the initiation of the isotretinoin treatment.…”
mentioning
confidence: 99%
“…Hence, it was deemed that, despite strong preclinical evidence, topical tazarotene is not an effective means of BCC chemoprevention in NBCCS patients. Retinoids have also been used to prevent malignancy in other skin cancer-predisposing genodermatoses, such as Muir-Torre syndrome and Bazex Syndrome [ 10 , 11 , 228 ]. Overall, chemoprevention with oral isotretinoin remains the primary off-label prophylactic for NBCCS and XP patients [ 10 ].…”
Section: Clinical Applications Of Retinoids For Keratinocyte Carcinom...mentioning
confidence: 99%